Qualitative Impact Assessment of CSA regional policy in Central America on agricultural sector institutions, investments and farmers (with P771) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
This study focused on the Central American Integration System which is a region integrated by eight countries: Guatemala, Honduras, Nicaragua, El Salvador, Costa Rica, Belize, Panama and Dominican Republic.